A Revolution A Day - Dockx, Nico (s.l. : s.n., 2015)
Abäke ; A Dog Republic ; Afif, Saâdane ; Aguirr y Otegui, Philip ; Arocha, Carla & Schraenen, Stéphane ; Bal-Blanc, Pierre ; Benhelima, Charif ; Bertocchi, Davide ; BLESS ; Bortolotti, Maurizio ; Bosmans, Kasper ; Brams, Koen ; Decavèle, Jean-Baptiste et al.
Beyond Boders, Contemporary Art by the Sea. Curated by: Lorenzo Benedetti , Patrick Ronse, Hilde Teerlinck and Phillip Van den Bossche The fifth edition of Beaufort entitled ‘Beyond Borders’ continues to build upon the tradition of art in the public space from the previous editions, but also makes a firm choice for change and innovation. The Province of West Flanders is the initiating party, and along with the Department of Culture has invited the ten coastal municipalities to support this inno- vative artistic concept and to help accomplish it. The artistic concept was developed by the curators Lorenzo Benedetti (De Appel in Amsterdam), Patrick Ronse (Be-Part in Waregem), Hilde Teerlinck (free- lance curator) and Phillip Van den Bossche (Mu.ZEE in Ostend). Production, implementation and supervi- sion are provided by a new coordination team estab- lished in Mu.ZEE: Anne Mouton, Laure-Anne Tillieux and Els Wuyts. Beyond Borders opts for a complete project along the coast, whereby a solo exhibition by the A Dog Republic collective led by 91-year-old architect, urbanist, and designer Yona Friedman is combined with a group exhibition at three locations in the province: the Zwin Nature centre along the east coast, Raversyde in the centre and visitor centre De Nachtegaal with the surrounding Oosthoek dunes along the west coast. The solo exhibition consti- tutes the artistic link between these three loca- tions, in order to complete the continuity of Beyond Borders in content and presentation.
cover holds together loose pages with text
Beaufort, Beyond Borders, 21.06 - 21.09.2015
boek